1984
DOI: 10.1007/bf02469641
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and clinical features of acute cholangitis accompanied by shock

Abstract: We investigated 91 cases of acute cholangitis, including 42 of severe cholangitis and 49 of mild cholangitis. The incidence of endotoxemia was 78.6 percent in 42 and 32.6 percent in the 49 patients. In the 42 with severe cholangitis, remarkable leukocytosis, thrombocytopenia, decrease of serum CH50, C3, plasma fibronectin and phagocytic index were characteristic. Disseminated intravascular coagulation (DIC) was observed in 76.2 percent. Since there was a positive correlation between platelet counts and levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Its clinical presentation ranges from mild forms responding to medical treatment to severe, life-threatening forms that require intensive care and urgent biliary drainage. Advances in intensive care, antibiotic treatment regimens, and biliary drainage techniques have dramatically improved the mortality rate of more than 50% prior to the 1970s [2,3] to less than 7% in the 1980s [4,5]. However, the mortality rate in severe cholangitis remains significant without appropriate management.…”
Section: Introductionmentioning
confidence: 99%
“…Its clinical presentation ranges from mild forms responding to medical treatment to severe, life-threatening forms that require intensive care and urgent biliary drainage. Advances in intensive care, antibiotic treatment regimens, and biliary drainage techniques have dramatically improved the mortality rate of more than 50% prior to the 1970s [2,3] to less than 7% in the 1980s [4,5]. However, the mortality rate in severe cholangitis remains significant without appropriate management.…”
Section: Introductionmentioning
confidence: 99%
“…Mild acute cholangitis improves with antibiotic therapy [4][5][6][7][8], but patients who do not respond to conservative treatment or those with moderate to severe cholangitis are likely to show rapid exacerbation of the condition, leading to considerably high morbidity and mortality [9,10]. This group of patients should be offered early biliary decompression along with systemic antibiotic treatment [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Shimada et al (13,14) reported that sepsis induced biliary tract infection in highly complicated DIC and/or multiple organ dysfunction. Therefore, therapeutic management of DIC in these patients should be a critical issue in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%